INTEGRATED DATA COLLECTION MODEL IN MOBILE INTERNET OF THINGS NET-WORKS - Savka, Maksym (Science-based technologies, 2025)
The Internet of things is considered a new stage in the development of the Internet, where data is exchanged between physical objects connected to the network, and each device can independently interact and establish connections with billions of other things. The basic concepts of the Internet of things are the organization of interaction between different objects in the environment, the transmission of information that they generate, and the provision of stable connections. Given the novelty, key features, and complexity of the IoT system structure, an important research tool at the design stage is the Mobile IoT network. A comprehensive data collection model based on the analysis of IoT and social IoT models and methods is proposed to improve the security of data collection and improve data management in IoT systems. This integrated model can be used in a variety of IoT applications, such as smart cities, smart transportation, smart buildings, and smart industry. It is noted that the cluster approach significantly increases energy efficiency and reduces network complexity. The proposed model improves management, reduces power consumption and latency, and has many advantages over existing data aggregation models in IoT networks. Various data collection protocols were analyzed in terms of latency, power consumption, security, and mobility support, and data routing methods were developed in dynamic IoT networks. Various data aggregation security models are described, such as access control, authentication, intrusion detection, and trust models, which are the basic mechanisms for building secure systems and are necessary elements of the proposed integrated model. The use of fogging techniques to reduce latency, increase throughput, and improve other network parameters is discussed.